Pengaruh Terapi Kognitif Perilaku Berbasis Kekuatan terhadap Peningkatan Resiliensi pada Remaja Panti Asuhan - Annisa Ridha Fadhillah; Qurotul Uyun; Indahria Sulistyarini (JIP (Jurnal Intervensi Psikologi), 2017)
This research is an experimental research aiming to understand whether strengths based cognitive behavioral therapy effectively improving resilience on adolescence orphanage. The subjects of this research were 15 adolescence orphanage from Sleman district who had a low to moderate level of resilience. Those 15 adolescence orphanage were divided into two groups, seven subjects from Orphanage X as the experimental group and other subjects from orpahange Y as the control group. The modules used for the training are based on four step of strengths based cognitive behavioral therapy of Padesky and Mooney (2012). This research used resilience scale adapted by researcher based on the original scale of resilience (Connor and Davidson, 2003). The data analysis of the research used independent sample t test method. The result showed that the strengths based cognitive behavioral therapy is effective to improve adolescence orphanage resilience. Therefore the hypothesis isaccepted.Key words: Strengths Based Cognitive Behavioral Therapy, Resilience, Adolescence Orphanage